2023
DOI: 10.1155/2023/4869006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Dietary α-linolenic Acid (18:3n-3) on the Growth Performance, Body Composition, and Fatty Acid Profile of Coho Salmon (Oncorhynchus kisutch) Alevins Cultured in Freshwater

Abstract: The present study evaluated the effects of supplemental dietary α-linolenic acid (ALA, 18:3n-3) on growth performance, body composition, hepatic fat metabolizing enzymes, and fatty acid profiles of coho salmon (Oncorhynchus kisutch) alevins cultured in freshwater. Six isonitrogenous and isolipidic experimental diets were formulated to attain different levels of ALA (0.09, 0.41, 0.76, 1.03, 1.32, and 1.68% dry weight) by adding linseed oil in a basal diet, respectively. Each diet was fed to triplicate groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The LSO-supplemented diet contained a higher content of ALA (16.30%) and total n-3 (16.63%), and this may satisfy the requirement of omega-3 and total n-3 of striped catfish, resulting in better growth of the fish group fed with the LSO diet compared with those of the others. In line with other study, Yu et al (2023) reported that the dietary ALA actively impacted fish growth performance, hepatic lipid metabolizing enzymes, and muscle fatty acid profile of Coho salmon, Oncorhynchus kisutch. In addition, in this study, the LSO diet contained a high level of total n-3 and a medium level of total n-6 (21.24%), which led to a balanced ratio of n-3/n-6 (0.90), while this ratio of the other diets was significantly low, ranging from 0.07 to 0.14.…”
Section: Discussionsupporting
confidence: 91%
“…The LSO-supplemented diet contained a higher content of ALA (16.30%) and total n-3 (16.63%), and this may satisfy the requirement of omega-3 and total n-3 of striped catfish, resulting in better growth of the fish group fed with the LSO diet compared with those of the others. In line with other study, Yu et al (2023) reported that the dietary ALA actively impacted fish growth performance, hepatic lipid metabolizing enzymes, and muscle fatty acid profile of Coho salmon, Oncorhynchus kisutch. In addition, in this study, the LSO diet contained a high level of total n-3 and a medium level of total n-6 (21.24%), which led to a balanced ratio of n-3/n-6 (0.90), while this ratio of the other diets was significantly low, ranging from 0.07 to 0.14.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, there were no differences in growth performances among the FO, SO and RO groups in our results, which is in line with previous studies on largemouth bass [ 17 , 18 ]. Other studies have proved that ALA can be converted by freshwater fish into LC-PUFA (long-chain polyunsaturated fatty acid), which is the necessary fatty acid for animal normal growth and development [ 36 ]. Combined with higher contents of ALA in FO, SO and RO, these three diets could supply enough substrate to synthesize LC-PUFA and then improve the growth of largemouth bass [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have proved that ALA can be converted by freshwater fish into LC-PUFA (long-chain polyunsaturated fatty acid), which is the necessary fatty acid for animal normal growth and development [ 36 ]. Combined with higher contents of ALA in FO, SO and RO, these three diets could supply enough substrate to synthesize LC-PUFA and then improve the growth of largemouth bass [ 36 , 37 ]. However, the PO and LO groups displayed lower growth performances in our results, which is in line with previously obtained results in European seabass [ 10 ] and bullfrog [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation